PENGARUH STRUKTUR UTANG TERHADAP KINERJA PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur Tahun 2011-2013) - Wempy Singgih Herdiyanto; Darsono Darsono (Diponegoro Journal of Accounting, 2015)
This research was aimed to test the effect of debt structure to firm performance. Dependent variable is firm performance represented by profitability rate with the indicator of return on asset (ROA). While independent variables consist of short-term debt to asset (STD), long-term debt to asset (LTD) and total debt to asset (TDA). Each measures with the data within this year and last year.Population  in  this  research  is  manufacture  companies  that listed  on  Indonesia  Stock Exchange from 2011 to 2013. Sampling method used in this research is purposive sampling. Data from 306 companies was taken as research samples. The data of this research analyzed using multiple regression model.The result of this research shows that last year TDA, last year STD and last year LTD don’t have any significant relation to firm performance. Otherwise significant result is gained from this year TDA, this year STD and this year LTD that they negatively have any relation to firm performance (ROA).